Is the shear wave sonographic elastography correlated with pain after breast augmentation with silicone implants an indication of inflammatory activity? A preliminary report - Paweł Rzymski; Mikołaj Kubasik; Michał Gaca; Tomasz Opala (Videosurgery and Other Miniinvasive Techniques)
Introduction: Formation of a capsule is a natural inflammatory response to a foreign body such as a breast implant.Breast capsular contracture is the most severe complication of implant surgery. Aim: To evaluate breast tissues and the periprosthetic reaction with sonoelastography. Material and methods: Nineteen patients aged 20-41 underwent breast augmentation with silicone-filled implants.Their 38 breasts were evaluated before surgery, and 7 and 14 days after surgery. Whole breast stiffness was measuredby applanation tonometry. Patients underwent shear wave elastography and Young’s moduli of breast tissues and theperiprosthetic capsule were estimated. During surgery patients underwent standard anaesthesia and were releasedhome 2 days later after removal of drainage. Each day, patients completed the pain visual analogue scale questionnaireseparately for left and right breasts. Results: Applanation tonometry did not correlate with any parameter. In shear wave elastography we observed statisticallysignificant changes in elasticity of all breast tissues with the highest values on day 7 after surgery and decreasingon day 14. The correlations between pain and capsule elasticity in lower quadrants measured were significantbetween days 4 and 10, whereas correlations of pain with applanation tonometry were insignificant. Glandular tissueelasticity in lower quadrants did not correlate with pain, whereas in upper quadrants there was a significant correlationon days 6-10. Fatty tissue, muscle and thoracic fascia elasticity did not correlate with breast pain. Breast implantvolume correlated with pain only shortly after surgery, but did not correlate with any sonoelastographic parameters. Conclusions: Breast pain correlates strongly with periprosthetic stiffness in elastography 4 to 10 days after breast augmentation,suggesting the possible role of an inflammatory reaction.